2008
DOI: 10.2174/092986608785133645
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization and Aggregation of Bovine Pancreatic Ribonuclease A:Backbone Hydration Probed by Infrared Band-Shift

Abstract: Protein hydration plays a crucial role in almost all aspects of biomolecular processes. In this research, we studied the hydration/dehydration-induced infrared amide I band-shift by using poly-L-lysine and bovine pancreas ribonuclease A as model polypeptides. It was found that a 1-4 cm(-1) shift could be clearly distinguished for all regular secondary structures during protein thermal unfolding. This shift was proven to be due to backbone hydration but not from experimental error, temperature effect or possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Decreases in the free energy of the bulk solvent are expected to favor the formation of solvent-shielded and oligomeric structures (40). In addition, desolvation is consistent with previous reports that hydration impedes amyloid aggregation (41)(42)(43)(44). Therefore, we believe that the simplicity of our model, combined with the fact that it offers a straightforward explanation for both the structural changes and the aggregation enhancement observed for proteins in TFE, make it a reasonable initial analysis.…”
Section: Desolvation May Initiate Protein Aggregation At Moderate [Tfe]supporting
confidence: 87%
“…Decreases in the free energy of the bulk solvent are expected to favor the formation of solvent-shielded and oligomeric structures (40). In addition, desolvation is consistent with previous reports that hydration impedes amyloid aggregation (41)(42)(43)(44). Therefore, we believe that the simplicity of our model, combined with the fact that it offers a straightforward explanation for both the structural changes and the aggregation enhancement observed for proteins in TFE, make it a reasonable initial analysis.…”
Section: Desolvation May Initiate Protein Aggregation At Moderate [Tfe]supporting
confidence: 87%
“…Zhang and Yan demonstrated aggregation coupled to dehydration for proteins in the presence of ethanol, and they suggested that similar effects should occur in TFE [25]. In addition, aggregation enhancement was observed when reverse micelles were used to limit water availability [26].…”
Section: Discussionmentioning
confidence: 99%
“…Spectra were normalized with concentration by Czarnecki and Wojtków [57] prior to 2D analysis. Lai et al [58] used the baseline correction, while Zhang and Yan [59] applied non-normalized Fourier self deconvolution before 2D analysis. Kamerzell et al [60] used several pretreatment steps, including the ATR effect correction, subtraction of water contribution, and normalization of concentration effect.…”
Section: Transformation and Pretreatment Of Datamentioning
confidence: 99%
“…Zhang and Yan [59] reported the 2D IR study of the H/D exchange reaction of bovine pancreas ribonuclease A. Distinction between deuterated and nondeuterated polypeptide chains was possible.…”
Section: H/d Exchange and Other Transformations Of Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation